Konten Vlog Sebagai Kebiasaan Komunikasi Siswa/I SMP Nusantara Plus - Prasetiyo Utomo, Fazar Alfian (Eastasouth Institute, 2023)
Vlog is an abbreviation of video blog. The contents of Vlog content are more about providing information. Speaking skill is the main key of Vlog type content. The purpose of this study was to determine the effect of Vlogs on YouTube on the communication behavior of SMP Nusantara Plus Students, Ciputat, South Tangerang. This research uses an explanatory survey method, with a quantitative approach. To get the number of research samples, the slovin formula was used. The total number of members of the Student population is 406 people, and after counting, the sample results are 80 people. The sampling technique uses non-probability sampling, a type of quota sampling. Primary data was obtained from respondents through a questionnaire with a measuring instrument in the form of a Likert scale. The results of the respondents' answers were processed using SPSS. Data were analyzed using simple linear regression analysis. The validity test used the Kaiser Mayer Olkin method and the reliability was measured using the Cronbach Alpha method. The results of this study show that Vlog content on YouTube has an influence of 36.1% on the communication behavior of SMP Nusantara Plus students. Students realize that watching Vlog-type content on YouTube is not only for entertainment purposes, but they also feel that they get some information from the Vlogs they watch. When communicating, the majority of students also imitate slang, body movements, and clothing styles like the vloggers they watch.